Biochemical comparison of rice wine produced using common and glutinous rice with three different traditional starter cakes - Kishneth Palaniveloo (2010)
Rice wine or `tapai' is one of the traditional alcoholic beverages, which has been produced in Sabah for ages and is used in most of the cultural rituals and ceremonies. This study delves on the chemical characterization of rice wine produced from common and glutinous rice using three different traditional starter cakes; 1) bitter, 2) bitter sweet, 3) sweet. Each batch of fermentation involving one type of rice and starter cake lasted for 4 weeks and the wine collected were separated from its rice, and the fermented rice was extracted in ethanol to yield crude extract. Sweet starter cake had the highest yeast/LAB load followed by bitter sweet and bitter and accordingly resulted in and weight reduction of substrate at an average of 450 %, 230 % and 210 % respectively. The volume of wine produced by glutinous rice was twice the volume produced by common rice. pH of the wines was in the range of 4.3 and 4.7. Morphological changes in the rice grain during fermentation were observed through scanning electron micrographs (SEM) and the presence of yeast/LAB growth and changes to the rice grains were observed. High Performance Liquid Chromatography analysis of the wine revealed that wine produced from common rice with its respective starter cake contained much lower glucose content [1) Bitter : 120.643 ± 0.21 mg/ml, 2) Bitter-Sweet : 270.42 ± 0.32 mg/ml, 3) Sweet : 310.326 ± 5.83 mg/ml] as compared to glutinous rice [1)Bitter : 300.274 ± 0.28 mg/ml, 2) Sweet and bitter : 320.251 ± 0.00 mg/ml, 3) Sweet : 440.138 ± 29.97 mg/ml]. However, gas chromatography analysis showed that rice wine produced from common rice had comparatively higher alcohol percentage; 9% to 12 % as compared to glutinous rice; 7% to 8 %. The difference in wine taste could be attributed to the varying type and amounts of organic acids and metabolites contained in the starter cakes and produced during the fermentation process. Gas Chromatography analysis revealed details of this complex composition. Comparison of these chemicals between their starter cake, wine and fermented rice is discussed. Ethanolic extract of the respective fermented rice contained low glucose levels but showed strong antioxidant and potent fibrinolytic enzyme activities, with bitter sweet starter cake displaying the best of results. Antioxidant potential of fermented rice extracts of common rice displayed higher scavenging activity compared to glutinous rice, while common rice wine displayed higher antioxidant values compared to glutinous rice wine. Fibrinolytic enzyme activities were present in fermented rice extracts, and extracts of common rice showed double the activity by diameter as compared to glutinous rice for all three starters. In summary, fermentation using different rice types with different starter cakes confirms the difference in chemical properties as well as bioactive potentials of the rice wine and fermented rice.